La présence à distance dans les pratiques enseignantes : le cas des robots de téléprésence - Dussarps, Clément; Lehmans, Anne; Gallon, Laurent; Dubergey, Françoise; Abénia, Angel (Éducation, Santé, Sociétés, 2020)
The use of mobile telepresence robots (RTM) is increasing in education, particularly primary and secondary, meeting the needs of disabled students (unable to attend school). This article examines the impact of these RTMs on high school students whose health does not allow them to go to class, often chronically and for a long time, with a particular focus on the feeling of presence and immersion and academic perseverance for these students over a few months. This study is based on a field survey (semi-structured interviews and online questionnaires), with a sample of six disabled pupils attending school in the Landes department
Publisher: Editions des archives contemporaines